DETERMINING NEW EXPORT GOALS AND COMPETITIVE STRATEGIES FOR THE JEWELRY INDUSTRY IN EAST JAVA IN A GLOBAL VALUE CHAIN PERSPECTIVE - Pranakusuma Sudhana (East Java Economic Journal, 2018)
Global Value Chain (GVC) is a relatively new concept where the process to produce goods or services occurs across countries. Previous research has concluded that integrating in GVC is important for a region to promote its economic growth. One indicator of a region's involvement in GVC is its export value at which in the Province of East Java, the jewelry industry (HS code 71) is the largest export contributor. This study aims to identify new export destinations based on trade data and to analyze internal factors of strength and weakness as well as external factors of opportunity and threat to formulate strategy to improve the competitiveness of jewelry industry with small, medium and large scale in East Java. In this research, the trade balance of jewelry industry between Indonesia and East Java and global importers was analyzed. The results show that some countries in Asia and Oceania, Europe and America are potential markets for the gold industry in East Java to increase the current value of exports. The geographical location of East Java which is close enough to the current export destination countries of jewelry products (Taiwan, Japan and Singapore) as well as potential destinations (India and China) is a competitive advantage. This research also identifies several strategies that can be done by the stakeholders in developing the jewelry industry in East Java.